Multipurpose Use of Geothermal Energy - Lienau, Paul J.; Lund, John W. (Oregon Institute of Technology (Klamath Falls, Or.), 1974)
The conference was organized to review the non-electric, multipurpose uses of geothermal energy in Hungary, Iceland, New Zealand, United States and the USSR. The international viewpoint was presented to provide an interchange of information from countries where non-electric use of geothermal energy has reached practical importance.